Factors Influencing the Entrepreneurial Interest of the Young Generation: An Empirical Review on Student Entrepreneurs - Irwan Suryadi; Andika Isma; Salim Diarra (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
In facing the era of global development and increasingly complex market demands, entrepreneurial interest among students is an important concern. The purpose of this research is to analyze the factors that influence student entrepreneurial interest. This study uses a qualitative approach that is descriptive analysis. The data collection techniques used are observation, interview, and documentation techniques. The research subjects amounted to 5 people consisting of students who are active and have a business. The results showed that there are five factors that can affect entrepreneurial interest, namely, income factors, family environment, community environment, entrepreneurship education and motivational factors. But of the five fakor the most influential is the income factor. Entrepreneurship can provide an opinion that can be used to meet the needs of his life, the desire to earn income that can lead to a person's entrepreneurial interest. The results of this study contribute relevant empirical thinking in understanding the factors driving entrepreneurial interest among students. Thus, this research is expected to be the basis for the development of strategies and supporting policies to increase entrepreneurial interest in the college environment.